Pengaruh Budaya Kerja dan Efektivitas Organisasi Terhadap Pelayanan Publik: (Studi pada Kantor Kecamatan Langkaplancar Kabupaten Pangandaran) - Kuswaya Kuswaya; Irma Bastaman (Jurnal Riset dan Inovasi Manajemen, 2024)
This research began with initial observations that showed that public services at the Langkaplancar District office were not optimal, so that the people served were not satisfied. Contributing factors include limited employee abilities and skills, suboptimal service, and slow service process. This study uses a quantitative descriptive method with a population of 8 employees in Langkaplancar District, Pangandaran Regency, using census techniques or saturated samples. Data is collected through questionnaires, interviews, and observations, as well as documentation of relevant activity and regulatory reports. The results of the study show that: Work culture has a positive and significant influence on public services; the better the work culture, the better the public service, the effectiveness of the organization also has a positive and significant effect on public services; the better the effectiveness of the organization, the better the public service, the work culture and the effectiveness of the organization together have a positive and significant effect on public services; The better the work culture and organizational effectiveness, the better the public service.